Traditional City Planning And its Impact on the Housing of the Same Family, Socially and Environmentally Dr. Khaled Bayazid - بايزيد خالد (Latakia University Journal -Engineering Sciences Series, 2021)
Change is inevitable and that the traditional planning of the city develops to respond to contemporary requirements in housing, mobility and social relations, and to devise new solutions in architectural planning and design that take into account cultural heritage and the current requirements of the most important priorities of the urban designer and architect today. Over time, the house was a response to the social and environmental requirements of man to achieve psychological and physical comfort, which helps him to practice his life in the correct manner so that he can give, creativity and establish healthy human relationships with others. The research reviewed the concept of traditional city planning and compared it to orthogonal network planning, the concept of single family housing in its heritage form, its environmental applications and its social goals, and how it helped to achieve social and environmental values, aspects and requirements, and how it was developed to express the spirit of the times by presenting some contemporary projects in this context and in order to respond to new concepts and values The harmony and twinning between the concept of closeness and openness in urban design or between individual and group values and the shared life sought by re-implanting urban concepts among architects and planners to create urban structures that help achieve the higher goals of life.